2018
DOI: 10.1090/mcom/3360
|View full text |Cite
|
Sign up to set email alerts
|

Structured backward error analysis of linearized structured polynomial eigenvalue problems

Abstract: We start by introducing a new class of structured matrix polynomials, namely, the class of M A -structured matrix polynomials, to provide a common framework for many classes of structured matrix polynomials that are important in applications: the classes of (skew-)symmetric, (anti-)palindromic, and alternating matrix polynomials. Then, we introduce the families of M Astructured strong block minimal bases pencils and of M A -structured block Kronecker pencils, which are particular examples of block minimal base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…The results in this work have already motivated considerable research in the area. For instance, they have clarified many of the results that have been published in the last few years on linearizations of matrix polynomials, since it has been proved in [10] that all generalized Fiedler linearizations [3,8,15], all Fiedler linearizations with repetition [7,11,74], and all generalized Fiedler linearizations with repetition [9] may be transformed through proper permutations into particular strong block minimal bases pencils that can be described very easily; structured versions of the backward error analysis in this paper have been developed for many classes of structured strong block minimal bases linearizations of structured matrix polynomials in [26]; in [62] particular block minimal bases linearizations have been used to compute efficiently and in a stable way the zeros of a polynomial that is the sum of two polynomials expressed in two different bases, as well as for solving other challenging numerical problems; extensions of block Kronecker pencils that linearize matrix polynomials expressed in Chebyshev bases have been developed in [48]; it has been shown that each strong block minimal bases pencil can be used to construct strong linearizations of rational matrices with non-constant polynomial part [2]; etc. In addition to these publications, several other ongoing research projects related to block minimal bases pencils are being currently developed by different researchers.…”
Section: )mentioning
confidence: 99%
“…The results in this work have already motivated considerable research in the area. For instance, they have clarified many of the results that have been published in the last few years on linearizations of matrix polynomials, since it has been proved in [10] that all generalized Fiedler linearizations [3,8,15], all Fiedler linearizations with repetition [7,11,74], and all generalized Fiedler linearizations with repetition [9] may be transformed through proper permutations into particular strong block minimal bases pencils that can be described very easily; structured versions of the backward error analysis in this paper have been developed for many classes of structured strong block minimal bases linearizations of structured matrix polynomials in [26]; in [62] particular block minimal bases linearizations have been used to compute efficiently and in a stable way the zeros of a polynomial that is the sum of two polynomials expressed in two different bases, as well as for solving other challenging numerical problems; extensions of block Kronecker pencils that linearize matrix polynomials expressed in Chebyshev bases have been developed in [48]; it has been shown that each strong block minimal bases pencil can be used to construct strong linearizations of rational matrices with non-constant polynomial part [2]; etc. In addition to these publications, several other ongoing research projects related to block minimal bases pencils are being currently developed by different researchers.…”
Section: )mentioning
confidence: 99%
“…The approach in Example 7.1 can be extended to other symmetric strong block minimal bases pencils of the symmetric polynomial part D(λ) of G(λ) = G(λ) T to construct other symmetric strong linearizations of G(λ), as long as D(λ) has odd-degree. See, for instance, the pencils considered in [14]. However, the linearization in Example 7.1 is particularly simple and, in view of the results in [7], we expect that it will have favourable numerical properties.…”
Section: Symmetric Strong Linearizations For Symmetric Rational Matricesmentioning
confidence: 99%
“…For the sake of brevity, we omit a detailed list of the many references published recently on linearizations of matrix polynomials and, instead, we invite the reader to check the references included in [10,14,43]. Unfortunately, this explosion of new classes of linearizations has not been followed by the corresponding analyses of their numerical properties, i.e., by the study of the errors they produce when they are used for solving numerically a PEP, and the number of papers analyzing this question is still low [1,44,14,15,23,24,39,45].…”
Section: Introductionmentioning
confidence: 99%